A Magneto-Microfluidic System for Investigating the Influence of an Externally Induced Force Gradient in a Collagen Type I ECM on HMVEC Sprouting. (August 2017) - Herath, Sahan C. B.; Sharghi-Namini, Soheila; Du, Yue; Wang, Dongan; Ge, Ruowen; Wang, Qing-Guo; Asada, Harry; Chen, Peter C. Y.
Advances in mechanobiology have suggested that physiological and pathological angiogenesis may be differentiated based on the ways in which the cells interact with the extracellular matrix (ECM) that exhibits partially different mechanical properties. This warrants investigating the regulation of ECM stiffness on cell behavior using angiogenesis assays. In this article, we report the application of the technique of active manipulation of ECM stiffness to study in vitro angiogenic sprouting of human microvascular endothelial cells (HMVECs) in a microfluidic device. Magnetic beads were embedded in the ECM through bioconjugation (between the streptavidin-coated beads and collagen fibers) in order to create a pretension in the ECM when under the influence of an external magnetic field. The advantage of using this magneto-microfluidic system is that the resulting change in the local deformability of the collagen fibers is only apparent to a cell at the pericellular level near the site of an embedded bead, while the global intrinsic material properties of the ECM remain unchanged. The results demonstrate that this system represents an effective tool for inducing noninvasively an external force on cells through the ECM, and suggest the possibility of creating desired stiffness gradients in the ECM for manipulating cell behavior in vitro.